The Magic School bus presents Planet Earth a nonfiction companion to the original Magic School Bus series - Jackson, Tom 1972- (Scholastic Inc., 2014)
Explore our unique, incredible planet with Ms. Frizzle's class! Packed with incredible photographs, amazing facts, and everything you ever wanted to know about fossils, rocks, minerals, volcanoes, stalagmites, stalactites, and much more!
"Based on The Magic School Bus books written by Joanna Cole and illustrated by Bruce Degen"--Title page verso
Keywords: Earth sciences / Juvenile literature; Earth (Planet) / Juvenile literature; Earth sciences; Earth (Planet); Sciences de la terre / Ouvrages pour la jeunesse; JUVENILE NONFICTION / Reference; JUVENILE NONFICTION / School & Education; JUVENILE NONFICTION / Science & Nature; Picture books; Picture books for children; Children's nonfiction; Literature; Juvenile works; Bilderbuch